2019
DOI: 10.1111/nph.15985
|View full text |Cite
|
Sign up to set email alerts
|

Calcium signals in guard cells enhance the efficiency by which abscisic acid triggers stomatal closure

Abstract: Summary During drought, abscisic acid (ABA) induces closure of stomata via a signaling pathway that involves the calcium (Ca2+)‐independent protein kinase OST1, as well as Ca2+‐dependent protein kinases. However, the interconnection between OST1 and Ca2+ signaling in ABA‐induced stomatal closure has not been fully resolved. ABA‐induced Ca2+ signals were monitored in intact Arabidopsis leaves, which express the ratiometric Ca2+ reporter R‐GECO1‐mTurquoise and the Ca2+‐dependent activation of S‐type anion chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 76 publications
(126 reference statements)
3
56
0
Order By: Relevance
“…As a measure of the reliability of our method in identifying cell type–expressed genes and of our ability to correctly annotate biological processes to a cell type, we compared a list of genes enriched in GCs in our analysis with a previous study that profiled GC functions. In agreement with these published reports (Gray, 2005; Lawson, 2009; Song et al, 2014; Niu et al, 2018; Huang et al, 2019), we found genes that respond to oxidative stress, salt stress, bacteria, cadmium ions and are involved in stomatal movement and photosynthesis, are preferentially expressed in GCs (Figure 4A and Figure S6). Our analysis further increased the spectrum of biological processes associated with GC development to include protein transport, vesicle-mediated transport, and cell death (Figure 4A and Figure S6).…”
Section: Resultssupporting
confidence: 93%
“…As a measure of the reliability of our method in identifying cell type–expressed genes and of our ability to correctly annotate biological processes to a cell type, we compared a list of genes enriched in GCs in our analysis with a previous study that profiled GC functions. In agreement with these published reports (Gray, 2005; Lawson, 2009; Song et al, 2014; Niu et al, 2018; Huang et al, 2019), we found genes that respond to oxidative stress, salt stress, bacteria, cadmium ions and are involved in stomatal movement and photosynthesis, are preferentially expressed in GCs (Figure 4A and Figure S6). Our analysis further increased the spectrum of biological processes associated with GC development to include protein transport, vesicle-mediated transport, and cell death (Figure 4A and Figure S6).…”
Section: Resultssupporting
confidence: 93%
“…The leaves were incubated in the bath solution (10 mM KCl, 1 mM CaCl 2 and 10 mM MES/BTP, pH 6) and illuminated with 100 µmol m −2 s −1 white light for at least 2 hr before the start of the experiment. Guard cells in the abaxial epidermis of intact leaves were applied with chitosan by using the current ejection technique (Huang et al, 2019), which the tip of a microelectrode was filled with 0.3 mg/mL of chitosan (or 10 mM of MES/BTP, pH6, as control), while the remaining part was filled with 300 mM KCl. The microelectrodes were connected to a custom-made amplifier (Ulliclamp01) via Ag/AgCl half-cells.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, AGB1 , which encodes a heterotrimeric G‐protein β‐subunit, was shown to be required for Ca 2+ sensing and calcium‐induced stomatal closure in Arabidopsis (Jeon et al ., 2019). Ca 2+ was also described to increase the efficiency of ABA‐triggered stomatal closure (Huang et al ., 2019), with intracellular Ca 2+ being monitored in this study using a genetically encoded Ca 2+ reporter R‐GECO‐mTurquoise (Waadt et al ., 2017). Using intracellular double‐barreled microelectrodes in intact Arabidopsis leaves, the authors report that Ca 2+ accelerates stomatal closure (Huang et al ., 2019).…”
Section: Roles Of Basal Aba Concentrations In Guard Cells and Basal Amentioning
confidence: 99%
“…Ca 2+ was also described to increase the efficiency of ABA‐triggered stomatal closure (Huang et al ., 2019), with intracellular Ca 2+ being monitored in this study using a genetically encoded Ca 2+ reporter R‐GECO‐mTurquoise (Waadt et al ., 2017). Using intracellular double‐barreled microelectrodes in intact Arabidopsis leaves, the authors report that Ca 2+ accelerates stomatal closure (Huang et al ., 2019). These findings correlate with Boolean modeling predictions (Albert et al ., 2017).…”
Section: Roles Of Basal Aba Concentrations In Guard Cells and Basal Amentioning
confidence: 99%